'One step closer': Acceptability of a programme of plasma donation for fractionation from men who have sex with men. Issue 7 (9th August 2019) - Caruso, Jessica; Germain, Marc; Godin, Gaston; Myhal, Geneviève; Pronovost, Frédérick; Morin, Michel; Otis, Joanne
Abstract : Background and objectives: In Canada, Héma‐Québec is considering the possibility of allowing men who have sex with men (MSM) to donate plasma for fractionation combined with a mandatory quarantine period. This study aims to assess the acceptability and operational feasibility of the programme in the targeted population. Materials and methods: Seven focus groups with MSM (N = 47) were conducted in Montréal, regarding their beliefs underlying attitudes, subjective norms and perceived behavioural control relating to intention to participate in a programme of plasma donation for fractionation. A theoretical thematic content analysis was realized. Results: Participants brought up benefits of the programme. Some are altruistic (help others, save lives, contribute as citizens), while others are linked to what it could bring to their community (progress, opportunity to include MSM in blood donation programmes, acknowledgement of MSM's contributions to the well‐being of others). However, even if the programme is in accordance with their altruistic values, it clashes with their values of equality and social justice. Many disadvantages were raised (discrimination and stigmatization of MSM, the fact that their blood is presented as being not as good as the blood of others). Facilitating factors and barriers to participation were put forward in terms of programme characteristics and sites where donations would be made. Conclusion: The findings suggest some interest in the programme of plasma donation for fractionation, but this is significantly tempered by the fact that differential treatment for MSM would continue and that their demands regarding access to whole blood donation are still unmet.